Studien zur räumlichen Differenzierung der Bevölkerung der Lombardei und Piemonts - Achenbach, Hermann (ERDKUNDE, 1976)
The spatial analysis of the population of Lombardy and Piedmont is concerned with a section of the economic core areas of Upper Italy. Inspite of industrialization both regions are characterized by their individual population development, the existence of which can be substantiated since the19th century. In Piedmont the political system of centralism established a strict division in the development of town and country, as well as a concentration of economic dynamism in the capital city of Turin. Following the French example the last century already witnessed a reduction in the size of families, accompanied by intensive emigration. By now the rural areas have a markedly ageing population structure. Lombardy, on the other hand, presents an age structure that closely resembles that of the national average for Italy. Notwithstanding the intense industrialization during the past 20 years there is still a considerable population surplus. Measured against the economic strength of the regions and the number of inhabitants, the immigration movements from the South are less than in Piedmont. Immigration and autochthonous population surpluses increase the effective economic strength of Lombardy. The boundaries of the differing population structures still remain strongly determined by the historic formation of the regions.